Diamond-Based Quantum Sensors for High-Resolution Magnetic Field Imaging of Neural Activity - Muhammad Firdaus A; Ethan Tan; Ava Lee (Yayasan Adra Karima Hubbi, 2025)
Advances in quantum sensing technologies have opened new opportunities for noninvasive, high-resolution detection of neural activity, particularly through diamond-based quantum sensors utilizing nitrogen–vacancy (NV) centers. Conventional neuroimaging techniques often face limitations in spatial resolution, temporal precision, and sensitivity to weak magnetic fields generated by neuronal currents. These constraints motivate the development of quantum-enhanced sensing approaches capable of capturing neural dynamics with unprecedented fidelity. This study aims to evaluate the performance of diamond-based quantum sensors for high-resolution magnetic field imaging and to assess their potential for real-time neural activity monitoring. A combined experimental and simulation-based methodology was employed, involving controlled magnetic field measurements using NV-center ensembles, calibration against established magnetometry systems, and computational modeling of neuronal magnetic signatures. The results show that NV-based sensors achieve sub-micron spatial resolution and detect magnetic fields in the nanotesla range, significantly outperforming traditional optical and electromagnetic techniques. The findings further demonstrate strong temporal responsiveness, enabling the reconstruction of fast neuronal firing patterns. The study concludes that diamond-based quantum sensors represent a promising frontier for next-generation neuroimaging, offering a scalable, minimally invasive platform for studying neural circuits with high spatial–temporal precision.